2022
DOI: 10.2478/hukin-2022-0103
|View full text |Cite
|
Sign up to set email alerts
|

Immediate Effect of Self-Modelling with Internal Versus External Focus of Attention on Teaching/Learning Gymnastics Motor-Skills

Abstract: The aim of this study was to identify the immediate effect of self-modelling with different focus of attention strategies (i.e., internal vs. external) on the teaching/learning of gymnastics motor-skills. Fifty-nine non-gymnast students participated in this study and were divided into three groups (i.e., an external focus group (EF), an internal focus group (IF), and a control group (CG)). Each participant’s performance of the back dismount in the parallel bars was assessed before the experiment (i.e., base-sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 31 publications
(41 reference statements)
1
3
0
Order By: Relevance
“…The results showed that both the external and internal focus groups performed better than the control group, with the external focus group showing the highest percentage of performance improvement. This study provides support for the use of external attentional focus in teaching and learning gymnastics techniques (10).…”
Section: Introductionsupporting
confidence: 55%
See 1 more Smart Citation
“…The results showed that both the external and internal focus groups performed better than the control group, with the external focus group showing the highest percentage of performance improvement. This study provides support for the use of external attentional focus in teaching and learning gymnastics techniques (10).…”
Section: Introductionsupporting
confidence: 55%
“…The previous research utilized self-modeling with only two practice sessions, while our study utilized skilled modeling with six practice sessions, held every other day. These differences in study design may have contributed to the varying results obtained in the two studies (10). Cognitive learning theory suggests that motor skills, as well as social skills, can be learned through observing the behavior of others.…”
Section: Discussionmentioning
confidence: 99%
“…Improving instructional models in coaching education can impact sports performance, increase the effectiveness of exercises performed, and reduce the risk of injuries. Several studies provide information on the benefits of using the appropriate attentional focus strategy, with researchers mainly investigating the impact of external and internal attentional focus strategies ( Amri-Dardari et al, 2022 ; Furuhashi et al, 2023 ). In contrast to the growing body of evidence showing that external and internal attentional focus strategies have distinct advantages, some new strategies for guiding athletes have appeared.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is possible that the benefits of the OEP can be attributed to additional elements such as the correct perception of the posture, the correct execution of the exercise through verbal guidance (command, sequence), and the understanding of the usefulness of the exercise, not just the execution of the exercise itself. Indeed, the importance of feedback during skill acquisition, the type of feedback and the frequency with which this is provided has been extensively discussed in the literature [31,32]. However, the efficacy of the time that this feedback and guidance is given is still unclear and the effectiveness of the OEP exercise guidance regarding delivery time on balance, gait, and cognition has never been explored.…”
Section: Introductionmentioning
confidence: 99%